The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1080/07853890.2018.1498118
|View full text |Cite
|
Sign up to set email alerts
|

Lipid lowering drugs and inflammatory changes: an impact on cardiovascular outcomes?

Abstract: Inflammatory changes are responsible for maintenance of the atherosclerotic process and may underlie some of the most feared vascular complications. Among the multiple mechanisms of inflammation, the arterial deposition of lipids and particularly of cholesterol crystals is the one responsible for the activation of inflammasome NLRP3, followed by the rise of circulating markers, mainly C-reactive protein (CRP). Elevation of lipoproteins, LDL but also VLDL and remnants, associates with increased inflammatory cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 227 publications
1
31
0
Order By: Relevance
“…The two major variables resulting from lipid lowering medications, i.e. reduction of LDL-C and hs-CRP in ASCVD patients appear to be additive as independent predictors [135,136]. In major statin trials, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The two major variables resulting from lipid lowering medications, i.e. reduction of LDL-C and hs-CRP in ASCVD patients appear to be additive as independent predictors [135,136]. In major statin trials, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…113 Of note, anti-PCSK9 monoclonal antibodies reverse the pro-inflammatory profile of monocytes in familial hypercholesterolaemia 114 and improve vascular inflammation. 115 Moreover, the observation that lower levels of PCSK9 are associated with reduced inflammation, especially in patients with the highest level of the inflammatory marker high sensitivity C-reactive protein (hs-CRP), 116 will need to be properly validated in specific clinical trials on inflammationassociated pathologies, as was done with the mAb canakinumab targeting interleukin-1b in the CANTOS anti-inflammatory thrombosis outcome study. 117 A recent meta-analysis reported a lack of effect of anti-PCSK9 therapy with mAbs on circulating hs-CRP levels, at least for the shortterm treatment, 118 and an analysis of the FOURIER trial showed that changes in hs-CRP levels were similar between evolocumab and placebo, even in subjects with a higher baseline hs-CRP level.…”
Section: Discussionmentioning
confidence: 99%
“…Roman and colleagues reported that administration of fenofibrate decreased arterial pressure in SS rats fed high salt diet with established hypertension and renal disease (Wilson et al, 1998). The exact mechanism by which fibrates lower arterial pressure is not completely understood but involves various pathways such as anti-lipidemic (Jonkers et al, 2001;Kim and Kim, 2020), anti-inflammatory (Feingold and Grunfeld, 2000;Diep et al, 2004;Ruscica et al, 2018), nitric oxide (Newaz et al, 2005;Ibarra-Lara et al, 2010;Esenboga et al, 2019;Xu et al, 2019), and 20-HETE (Roman et al, 1993;Wilson et al, 1998). In the current study, we cannot exclude the impact of any of these pathways on reducing arterial pressure in response to gemfibrozil treatment.…”
Section: Discussionmentioning
confidence: 99%